2021
DOI: 10.3389/frwa.2021.628955
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Assessment of Check Dam Performances in Semi-Arid Areas: A Case Study From Gujarat, India

Abstract: In semi-arid India, managed aquifer recharge (MAR) is often used to enhance aquifer storage, and by implication, water security, and climate resilience, by capturing surface runoff, mainly through check dams implemented at the community level. Despite their extensive use, the design of these structures typically does not follow a systematic method to maximize performance. To aid in the improvement of check dam design parameters and location siting, we develop a dynamic tool, which integrates the daily water ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Recent research has shown that this significantly impacted CDs functioning with recharge in dry years being very limited and insufficient to meet the irrigation demand in the catchment (Alam et al, 2022b). Mozzi et al (2021) have reported similar dynamics with the number of fillings being lowest in the dry years, followed by normal and wet years. However, they did not account for CDs in series so this could even be lower, especially in dry years when runoff is limited (Alam et al, 2022b).…”
Section: Questionnairementioning
confidence: 90%
See 2 more Smart Citations
“…Recent research has shown that this significantly impacted CDs functioning with recharge in dry years being very limited and insufficient to meet the irrigation demand in the catchment (Alam et al, 2022b). Mozzi et al (2021) have reported similar dynamics with the number of fillings being lowest in the dry years, followed by normal and wet years. However, they did not account for CDs in series so this could even be lower, especially in dry years when runoff is limited (Alam et al, 2022b).…”
Section: Questionnairementioning
confidence: 90%
“…However, these benefits are mostly accrued in wet years and are least in dry years (Figure 3A) when irrigation demand is the highest. This is due to limited rainfall and runoff in the dry years that limits inflows to the CDs (Alam et al, 2022b;Mozzi et al, 2021). Thus the duration of water availability in CDs decreases from 8 months in wet years to only 3 months in dry years (Figure 3B).…”
Section: Drought Impact Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of high E.C. and Cl − values is indicative of seawater intrusion, which is a serious degradation factor for coastal aquifer systems [32]. According to the seasonal variations, Cl − presents higher concentrations during the dry period for most of the samples.…”
Section: Basic Chemical Analysismentioning
confidence: 96%
“…Two methods to estimate the WA i were tested. The first is the formula by Mozzi et al [39], devised to estimate the recharge from check dams in India. According to these authors, the wetted area can be computed through Equations ( 2) and (3).…”
Section: Wetted Area (Wa I )mentioning
confidence: 99%